Temporal trends of organophosphate esters in a sediment core from the tidal flat of Liao River estuary, Northeast China - Luo, Qing; Wang, Congcong; Gu, Leiyan; Wu, Zhongping; Li, Yujie (Frontiers in Marine Science, 2023)
The historical trends and inventory of organophosphate esters (OPEs) were investigated based on depth profiles of OPEs in sediment core collected from the tidal flat of the Liao River estuary in northeastern China. The concentration of ∑13OPEs in sediment core has increased continuously since records began, reaching a peak of 10.8 ng g-1 dry weight (dw) in the 1960s, then began to decline and fall to a low of 3.91 ng g-1 dw in the 1980s, before rising again and increasing to 20.4 ng g-1 dw in the 2000s. After a brief decline, It started to increase again and reached a peak of 27.0 ng g-1 dw in 2018. Tributyl-n-phosphate was found in each layer of the sediment core, accounting for 31.9 - 100% of ∑13OPEs. The fluxes of OPEs ranged from 46.5 to 105 ng cm-2 y-1 in the sediment layers deposited between 2007 and 2018. The inventory of OPEs in the sediment core was estimated to be 1541 ng cm-2. This work reports for the first time the historical contamination trends of OPEs in Chinese sediments, which is important for assessing the environmental risk of OPEs.